Implementasi Digital Marketing Untuk Produk BRI Mobile Banking (Brimo) Pada Bank BRI KCP Kemang Pratama - Indra Muis; Wiwit Septi Ratika Putri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
The use of mobile banking applications such as BRIMO by individuals aged 55 and above is often confronted with several challenges. Limitations in technology use are one of the main hurdles, where understanding application navigation, utilizing online transaction features, and digital security measures can be complex. This research aims to implement digital marketing through digital technology such as websites, social media platforms like Instagram, Twitter, YouTube, SEO, email marketing, etc., to facilitate customers in becoming familiar with, using, and understanding BRIMO features. Using a qualitative approach, through interviews and direct observation, as well as segmenting customers based on generations: generation millennials (18-34 years old), generation X (35-54 years old), Babyboomers (55 years old and above), generation Z (below 18 years old). Marketing mix analysis of the 7P by determining product, price, promotion, place, people, physical evidence, process. Findings indicate that customers aged 55 and above, who are less familiar with technology, face difficulties in using BRIMO. Therefore, a proposal is made to create video tutorials on how to use the application and its features on BRIMO, promoted through social media channels such as YouTube. Keywords: Customer, Digital Marketing, Marketing Mix, Mobile Banking